Rationalization of work of leaders of physical-sports organizations - Путятіна, Галина Миколаївна (Slobozhanskyi Herald of Science and Sport, 2016)
Putyatina G. Purpose: to create the main ways of rationalization of the work of heads of physical-sports organizations in the structure of their scientific organization of the work. Material & Methods: the content of the administrative activity of representatives of the system of the regional government of the sphere of physical culture and sport of the Kharkov area, and also directors of sports schools of Kharkov (57 respondents) are generalized. Methods – the analysis of references, the organizational analysis, the organizational diagnosis, the poll (questioning), the methods of mathematical statistics. Results: the essence and the content of rationalization of the administrative work in the sphere of physical culture and sport are considered. The integrated approach to certain objects of rationalization of the administrative work is established in physical-sports organizations. Conclusions: the main ways of rationalization of the work of heads of physical-sports organizations are: the organization of work concerning the development of motivational mechanisms of the activity of heads; the increase of the economic appeal of work; the formation of ideology of a healthy lifestyle.